2019
DOI: 10.1111/jam.14352
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus licheniformis , a potential probiotic, inhibits obesity by modulating colonic microflora in C57BL/6J mice model

Abstract: Aims: This study evaluated the effects of a potential probiotic, Bacillus sp., on the growth, serum and hepatic triglyceride, histological features of liver tissues and colonic microflora in high-fat diet-induced obese mice. Methods and Results: Sixty male C57BL/6J mice were randomly divided into five groups: mice fed a low-fat diet (Cont), mice fed a high-fat diet (Hf), Hf and orally challenged with Bacillus subtilis (Bs), B. licheniformis (Bl) and a mixture of B. subtilis and B. licheniformis (Bls). Gavage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…The policy for B. licheniformis is different in different countries. B. licheniformis is not registered for foods in Korea while it is available in a dried form as a probiotic in China [22,23]. B. licheniformis needs to be studied more to determine its toxicity for use as foods since some strains of B. licheniformis have probiotic activities, and chungkookjang fermented with B. licheniformis improves the bioactivities in animal studies [24].…”
Section: Toxic Bacillus Species Potentially Existing In Chungkookjangmentioning
confidence: 99%
“…The policy for B. licheniformis is different in different countries. B. licheniformis is not registered for foods in Korea while it is available in a dried form as a probiotic in China [22,23]. B. licheniformis needs to be studied more to determine its toxicity for use as foods since some strains of B. licheniformis have probiotic activities, and chungkookjang fermented with B. licheniformis improves the bioactivities in animal studies [24].…”
Section: Toxic Bacillus Species Potentially Existing In Chungkookjangmentioning
confidence: 99%
“…Although the use of probiotic strains of Bacillus is still recent, emerging studies have described the health benefits associated with their ingestion [20,21]. For instance, probiotic strains of Bacillus were shown to provide protective effects against high fat diet-induced metabolic disorders in mice [22] and anti-obesity effects [23]. However, relatively few studies have examined the possible synergistic effect between fermented foods and a specific Bacillus species.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota is strongly shaped by HFDs, and obese humans and animals are characterized by low gut microbial diversity and impaired gut microbiota compositions, especially in terms of Firmicutes and Bacteroidetes abundances (18)(19)(20)(21)(22)(23)(24)(25). Interestingly, several reports have revealed that the gut microbiota and its metabolites exhibit circadian rhythms, which are driven by HFDs (26)(27)(28)(29)(30).…”
mentioning
confidence: 99%